PERSEPEKTIF SOSIAL DAN POLITIK TERHADAP KEBANGKITAN PEMBANGUNAN EKONOMI MELALUI KEPEMIMPINAN ABU BAKAR AL- SHIDDIQ DAN UMAR IBN AL-KHATTAB - Faisal Faisal; Abdul Mukti; Zaini Dahlan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2022)
Basically humans are born as leaders, since Adam was created as a caliph to be assigned to take care of the earth, the word caliph itself can be interpreted as a liaison or leader to convey to lead something. As a leader, his expertise is required in regulating the behavior of others in his work by using power. Leaders have the right to power to direct, mobilize, and influence the people they lead to carry out orders that must be carried out in achieving a desired goal. Therefore, a leader must have good leadership skills, so that harmony will be achieved in a leadership, and the goals that have been outlined will also be achieved. In connection with this leadership, Islam began a leadership with the sending of Muhammad SAW as a prophet and apostle to invite people to the truth, embrace Islam as a belief. In the course of the struggle and spread of Islam, the prophet Muhammad automatically became the leader of the Muslims until the end of his life. After the death of the Prophet Muhammad, the Muslims were afflicted with deep sadness, they lost a beloved leader, a leader who had a unique and complex personality, broad-minded, and trustworthy.